2003
DOI: 10.1088/0957-4484/14/5/309
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and crystalline phase study of electrospun TiO2 SiO2nanofibres

Abstract: Nanofibres of TiO2–SiO2  (Ti:Si = 50: 50 mol%) with diameters of 50–400 nm were prepared by calcining electrospun nanofibres of polyvinyl acetate (PVac)/titania–silica composite as precursor. These PVac/titania–silica hybrid nanofibres were obtained from a homogenous solution of PVac with a sol–gel of titanium isopropoxide (TiP) and tetraethoxysilane by using the electrospinning technique. The nanofibres were characterized by scanning electron microscopy (SEM), wide-angle x-ray diffraction (WAXD), Fourier tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 34 publications
3
99
1
Order By: Relevance
“…The BET surface areas, pore diameters, and total pore volumes of inorganic porous silica fibers are shown in showed much larger surface area than that of the inorganic fibers prepared with sol-gel [20].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The BET surface areas, pore diameters, and total pore volumes of inorganic porous silica fibers are shown in showed much larger surface area than that of the inorganic fibers prepared with sol-gel [20].…”
Section: Resultsmentioning
confidence: 88%
“…The electrospun inorganic nanofibers containing SiO 2 componenet have been reported by electrospinning the polymer with sol-gel solution [20,25], sol-gel solution [26], and polymer solution blended with colloidal silica particles [27], respectively. However, to our best knowledge, the SiO 2 nanofibers with ultra-high surface area and porosity are difficult to find in periodicals and monographs.…”
Section: Introductionmentioning
confidence: 99%
“…The uniformity of contrast suggested that TiO 2 nanoparticles with average dimensions from 10 to 60 nm were dispersed in the PPV fiber matrices, and XRD patterns revealed that TiO 2 existed mainly as an amorphous structure. [2] More evidence of the existence of TiO 2 in the hybrid fibers was provided by EDS, presented in Figure 2(b). The Ti and O peaks were observed at 0.548eV and 4.535eV, corresponding to the expected values for Ti bound to O, which also indicated the existence of TiO 2 in the polymer fibers.…”
Section: Resultsmentioning
confidence: 92%
“…The fabrication of these materials in 1D using self-assembly and electrospinning techniques has been studied by many groups looking at organic, inorganic and inorganic/organic materials. [1][2][3] Recently, much attention has been focused on synthesizing nanoparticle-supported nanofibers by electrospinning a nanoparticle-containing polymer solution or inorganic/ polymer solution, [4] with materials such as TiO 2 / PVP, [5a] V 2 O 5 -TiO 2 /PVP, [5b] TiO 2 -SiO 2 /PVac [2] , CdS/PVP, [5c] copper/PVA [5d] and PbS/polymer [5e] fibers by stepwise growth, self-assembly via gas deposition and calcination processes. Among the inorganic compounds, TiO 2 as an indirect band gap material has recently been of substantial interest for both industrial applications and scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…shows the presence of OH stretching vibration (Burgos et al, 1999), while the IR band at 1631 cm -1 is ascribed to Si-H 2 O adsorption (Ding et al, 2003;Wang et al, 2007). The peak at 1404 cm -1 corresponds to O-H bending mode (B. P. , the band at 1019 cm -1 corresponds to Si-OH and Si-O-Ti vibration modes (Zhai et al, 1999) while a Ti-O-Ti band appears at 787 cm -1 .…”
Section: Ftirmentioning
confidence: 99%